2007
DOI: 10.9795/bullgsj.58.389
|View full text |Cite
|
Sign up to set email alerts
|

Umber and manganese deposits in the Northern Shimanto Belt, west Kii Peninsula, Japan, with special reference to sedimentary environment and rare earth resources.

Abstract: Abstract:To evaluate resource potential of rare earth elements (REE), umber (ferromanganese sediment), manganese ore and associated rocks such as basalt, chert and shale in the Itogo, Misoigawa, Usugaokayama, Komoridani and Ryujin areas in the Northern Shimanto Belt, SW Japan were examined. The umber in the Itogo area and manganese ore in the Ryujin area occur between a basaltic footwall and a hanging wall shale.The basalts from the five areas are altered, resulting in addition of water and alkaline elements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The mineralogy and texture of these ores are different from those of the cherthosted manganese ores. Rare earth, major and trace element geochemistry on these deposits showed that the geochemical features of these ores are similar to those of modern submarine hydrothermal deposits suggesting that they were precipitates by submarine hydrothermal activity (Choi and Hariya, 1992;Nozaki et al, 2004;Kato et al, 2005a,b;Fujinaga et al, 2006;Moriyama et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The mineralogy and texture of these ores are different from those of the cherthosted manganese ores. Rare earth, major and trace element geochemistry on these deposits showed that the geochemical features of these ores are similar to those of modern submarine hydrothermal deposits suggesting that they were precipitates by submarine hydrothermal activity (Choi and Hariya, 1992;Nozaki et al, 2004;Kato et al, 2005a,b;Fujinaga et al, 2006;Moriyama et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…The Ryujin deposits occur between basalt and red or black shale. Moriyama et al (2007) measured the rare earth and trace element compositions of the basalt and manganese ore, and suggested that basalt is mid-oceanic ridge basalt in origin and the manganese ore was formed from hydrothermal solution near the mid-oceanic ridge. The manganese ore consists of rhodochrosite, caryopilite, braunite and hematite (Yoshimura, 1969;Takimoto and Ishigaki, 1973).…”
Section: Kii Peninsula (Shimanto Chichibu and Sanbagawa Belts)mentioning
confidence: 99%
“…The composition of stratiform manganese and ferromanganese ores from Phanerozoic accretionary complexes in the Japanese Islands (Kato et al , 2005a, b; Fujinaga et al , 2006; Moriyama et al , 2007a, b) is notably different to that of the IOG ores (Fig. 3).…”
Section: Chemical Composition Of Iog Ore Samplesmentioning
confidence: 99%
“…Data sources: Mahapatra et al (1996), Mishra et al (2006) and the present study for the Iron Ore Group (IOG) ores. Choi and Hariya (1990), Kato et al (2005a, b), Fujinaga et al (2006) and Moriyama et al (2007a, b) for the Japanese ore data.…”
Section: Chemical Composition Of Iog Ore Samplesmentioning
confidence: 99%
See 1 more Smart Citation